Patient-centered endometriosis care implementation at tertiary and secondary care hospitals in Indonesia - Achmad Kemal Harzif; Beryliana Maya Anisa; Eva Suarthana; Cut Rika Maharani; Rusnaidi; Hilwah Nora; Rajuddin; Ade Permana; Heidi Dewi Mutia; Nafi'atul Ummah; Putri Nurbaeti; Aisyah Retno Puspawardani; et al. (Heliyon)
Background: Endometriosis has a high recurrence rate within five years (40–50 %). High recurrence remarkably reduces Health-Related Quality of Life (HRQOL). Patient-centered endometriosis care (PCEC) is a range of care that respects the patient's preferences and needs while being guided by the patient's values and may provide better treatment for patients. Our study is the first to evaluate the implementation of PCEC in Indonesia. Materials and methods: We evaluated PCEC at Dr. Cipto Mangunkusumo Hospital in Jakarta (Center-1), Raden Mattaher Hospital in Jambi, and dr. Zainoel Abidin Hospital in Aceh (Center-2) from October 2021 to May 2022. Center-1 represented tertiary care, and center-2 represented secondary care. This study used the ENDOCARE Questionnaire (ECQ) instrument, which produced mean important score (MIS), percentage of negative performance (PNP), and patient-centeredness score (PCS) as outcomes. Higher PCS reflects greater patient-centered care of the center. Results: A total of 73 patients were recruited and divided into two groups of centers. Patients from Center-1 had significantly higher patient-centeredness scores vs. patients in centers without the training and guideline: dimension ''Respect for patients' values, preferences, and needs'' (Center-1 7.33, 6–10, Center-2 6, 6–6; p < 0.001), dimension ''Coordination and integration of care'' (Center-1 6, 4.44–8.67, Center-2 5.5, 4–6; p = 0.006), dimension ''Information, communication, and education'' (Center-1 7.14, 6–8.29, Center-2 5.14, 5.14–6; p < 0.001), dimension ''Physical comfort'' (Center-1 6, 6–8, Center-2 6, 6–6; p = 0.033), dimension ''Endometriosis clinical staff'' (Center-1 6, 6–9, Center-2 6, 6–6, p = 0.049). Subjects with higher education and experienced endometriosis recurrences statistically had higher patient-centeredness scores. Conclusion: Our findings suggest that endometriosis training and having endometriosis clinical guidelines could improve patients' experience in receiving PCEC. Information for patients should be made simple so they can understand the purpose of the treatment.